Specific Microbial Taxa and Functional Capacity Contribute to Chicken Abdominal Fat Deposition - Xiang, Hai; Gan, Jiankang; Zeng, Daoshu; Li, Jing; Yu, Hui; Zhao, Haiquan; Yang, Ying; Tan, Shuwen; Li, Gen; Luo, Chaowei; Xie, Zhuojun; Zhao, Guiping; et al. (Frontiers in Microbiology, 2021)
Genetically selected chickens with better growth and early maturation show an incidental increase in abdominal fat deposition (AFD). Accumulating evidence reveals a strong association between gut microbiota and adiposity. However, studies focusing on the role of gut microbiota in chicken obesity in conventional breeds are limited. Therefore, 400 random broilers with different levels of AFD were used to investigate the gut microbial taxa related to AFD by 16S rRNA gene sequencing of 76 representative samples, and to identify the specific microbial taxa contributing to fat-related metabolism using shotgun metagenomic analyses of eight high and low AFD chickens. The results demonstrated that the richness and diversity of the gut microbiota decrease as the accumulation of chicken abdominal fat increases. The decrease of Bacteroidetes and the increase of Firmicutes were correlated with the accumulation of chicken AFD. The Bacteroidetes phylum, including the genera Bacteroides, Parabacteroides, and the species, B. salanitronis, B. fragilis, and P. distasonis, were correlated to alleviate obesity by producing secondary metabolites. Several genera of Firmicutes phylum with circulating lipoprotein lipase activity were linked to the accumulation of chicken body fat. Moreover, the genera, Olsenella and Slackia, might positively contribute to fat and energy metabolism, whereas the genus, Methanobrevibacter, was possible to enhance energy capture, and associated to accumulate chicken AFD. These findings provide insights into the roles of the gut microbiota in complex traits and contribute to the development of effective therapies for the reduction of chicken fat accumulation.